Introduction to the Special Issue: A Macromarketing Perspective on Alternative Economies. (June 2017) - Campana, Mario; Chatzidakis, Andreas; Laamanen, Mikko
Alternative economies respond to the precarious conditions underpinning the everyday lives of individuals, and their lack of access to and scarcity of resources and competences. Recently there has been increasing interest in the field of macromarketing towards such alternative forms of exchange and marketplaces. Nonetheless, current studies of alternative economies remain fragmented. The objective of this special issue is to advance our understanding of alternative economies and stimulate future research within this domain. Seven articles are included in this special issue of the Journal of Macromarketing . Each article presents forward-looking research exploring one of three aspects of alternative economies: (1) the paradigms used within alternative economies, (2) the institutional logics that guide action within these systems and (3) the implications to individuals, localities, markets, and society. The editors of the special issue briefly introduce the topic, provide a definition of alternative economies, offer an overview of the articles and their contributions, and direction for future research bringing together alternative economies and macromarketing.